Which combination of medical expulsive therapy is more effective for treatment of distal ureteral stone in adults? A systematic review and network meta-analysis - Maryam Taheri; Nasrin Borumandnia; Hamidreza Abdi; Amir H Kashi; Setareh Nourani; Sogand Sheikholeslami; Yasamin Maleki Gilvaei; Pardis Ziaeefar; Abbas Basiri (BMC Urology)
Abstract Background Medical Expulsive Therapy (MET) has been recommended as an established modality for the treatment of distal ureteral stones due to its clearance rate, pain control, and patient satisfaction while having minimal morbidity in comparison to other urologic interventions. In some studies, a combination of medications has been used, which we assessed in this network meta-analysis (NMA). Methods We conducted systematic searches in PubMed, Scopus, and Web of Science to identify relevant trials published between 2001 and 2024. We excluded articles that looked at MET for upper ureteral stone passage or after shock wave lithotripsy (SWL). NMA was performed to compare the effect of combination MET on stone expulsion rate (SER), stone expulsion time (SET), and need for analgesia. Results We included 19 studies with 2414 participants. NMA results revealed that the combination MET of α-blockers with PDE-5 inhibitors (OR = 2.7, CI = 1.80,4.05), corticosteroids (OR = 2.7, CI = 1.81,4.13), and phytotherapy (OR: 3.10, CI = 1.62,5.92) were more effective than α-blockers alone in SER. The combination MET of α-blockers with PDE-5 inhibitors (MD: -3.8, CI=-7.0, -0.5) showed significantly lower SET compared to α-blockers alone. Finally, combination MET of α-blockers with PDE-5 inhibitors (MD:1.0, CI = 0.4,1.7) and nifedipine with corticosteroids (MD:1.2, CI = 0.4,1.9) showed a significant decrease in analgesia use. Conclusions The combination MET of α-blockers with PDE-5 inhibitors, corticosteroids, and phytotherapy increases the rate of stone clearance 2.7 to 3.1 times more than α-blockers alone. The other benefits of combination MET were lower expulsion time and less analgesia use that needs further studies.